The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1002/jbm.b.30170
|View full text |Cite
|
Sign up to set email alerts
|

Porcine small intestine submucosa (SIS) is not an acellular collagenous matrix and contains porcine DNA: Possible implications in human implantation

Abstract: Porcine small intestinal submucosa (SIS) has been recommended as a cell-free, biocompatible biomaterial for the repair of rotator cuff tendon tear. However, we have observed noninfectious edema and severe pain in patients who have undergone SIS implantation for tendon repair. The aim of this study was to conduct an independent assessment of the safety and efficacy of Restore SIS membrane. The Restore orthobiologic implant was examined by histology and the nested PCR technique using porcine immunoreceptor DAP12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
295
0
9

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 387 publications
(313 citation statements)
references
References 13 publications
9
295
0
9
Order By: Relevance
“…21 Because of this, both SIS and GJ are suitable candidates as scaffolds for tendontissue-engineered therapies, because they may provide a natural three-dimensional scaffold for cell and tissue growth, and the presence of growth factors, such as bFGF or TGF-b1, have mitogenic effects on cells and stimulate ECM synthesis. 10 In summary, results of the present study together with the recent concerns on the clinical use of SIS, because of side effects observed in patients, 14,38 support the conclusion that GJ represents more appropriate characteristics than SIS to be used for rotator cuff tendon healing and as a scaffold for in situ tissue engineering and for the in vitro bioengineering of tendons for the regeneration of massive rotator cuff tears. Tenocytes isolated from tendons of animals submitted to GC systemic administration showed a lower proliferation rate and metabolic activity compared with tenocytes from healthy tendons.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…21 Because of this, both SIS and GJ are suitable candidates as scaffolds for tendontissue-engineered therapies, because they may provide a natural three-dimensional scaffold for cell and tissue growth, and the presence of growth factors, such as bFGF or TGF-b1, have mitogenic effects on cells and stimulate ECM synthesis. 10 In summary, results of the present study together with the recent concerns on the clinical use of SIS, because of side effects observed in patients, 14,38 support the conclusion that GJ represents more appropriate characteristics than SIS to be used for rotator cuff tendon healing and as a scaffold for in situ tissue engineering and for the in vitro bioengineering of tendons for the regeneration of massive rotator cuff tears. Tenocytes isolated from tendons of animals submitted to GC systemic administration showed a lower proliferation rate and metabolic activity compared with tenocytes from healthy tendons.…”
Section: Discussionsupporting
confidence: 78%
“…21 However, so far, few studies have been done on rotator cuff tendon regeneration by means of in situ tissue engineering and in vitro bioengineering of tendons as compared to the extensive work on bone and cartilage. 6,14,[22][23][24][25] This previous literature review, showed the necessity for future studies in this area, and, therefore, an in vitro study was performed by isolating tenocytes from the rotator cuff of normal and GC-treated rats. The tenocytes were cultured on two collagenous membranes and cell proliferation and function were recorded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, apart from the excellent biocompatibility of the natural ECM, growth factors preserved in the decellularized matrix may further facilitate cell growth and remodeling [9]. Nevertheless, cell seeding in decellularized ECM may also lead to inhomogeneous distribution while incomplete removal of cellular components may elicit immune reactions upon implantation [129].…”
Section: Scaffolding Approaches In Tissue Engineeringmentioning
confidence: 99%
“…Allogenic ECMs can still contain some DNA from their allogenic source and may induce inflammatory responses in the host [22]. These inflammatory responses can cause pain and edema at the site of repair and may increase the degeneration of the rotator cuff repair that has been documented in the initial degenerative process of the rotator cuff [59]. They are also less elastic than autogenic tendon, which may result in comparably increased retear rates due to decreased load-carrying abilities [14].…”
Section: Ecm Augmentationmentioning
confidence: 99%